2017
DOI: 10.12688/f1000research.12474.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining access to oral health services among children aged less than 12 years in Peru

Abstract: Background: Understanding problems of access to oral health services requires knowledge of factors that determine access. This study aimed to evaluate factors that determine access to oral health services among children aged <12 years in Peru between 2014 and 2015. Methods: We performed a secondary data analysis of 71,614 Peruvian children aged <12 years and their caregivers. Data were obtained from the Survey on Demography and Family Health 2014-2015 (Encuesta Demográfica y de Salud Familiar - ENDES). Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 28 publications
(23 reference statements)
0
25
0
3
Order By: Relevance
“…The process of study selection is shown in Figure 1 (flow chart [21]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [22][23][24][25][26][27][28][29][30][31] and 31 studies investigating adults ). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of study selection is shown in Figure 1 (flow chart [21]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [22][23][24][25][26][27][28][29][30][31] and 31 studies investigating adults ). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
“…The process of study selection is shown in Figure 1 (flow chart [ 21 ]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and 31 studies investigating adults [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in Brazil, though access to UHC significantly reduced infant mortality rate, the prevalence of ECC in children up to 5 years of age was still very high [37]. In Peru, access to UHC had no impact on the oral health of children under 12 years of age [38]. However, studies in South Africa and Nordic countries reported that access to free oral health care reduced caries severity in children [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, dental health‐related knowledge, attitudes, and behaviors among caregivers of high‐risk children are found to be inadequate . Lower education levels and social status of caregivers were associated with irregular child visits and poor access to dental professional services . A Mexican study showed that mothers' self‐efficacy was associated with their children's oral health …”
Section: Introductionmentioning
confidence: 99%